New strategy for new times – the necessity of redefining the EU foreign policy in its neighbourhood (Economic and Political Thought, 2015)
Transformations of the international environment we are facing nowadays,force the EU to verify its policy on the international arena. The Russian-Ukrainian conflict and a huge wave of immigrants from the war-affectedareas of the Middle East (especially Syria) require the development of a newstrategic approach by the Union. The previous EU assumptions formulated inthe European Security Strategy (ESS) and in the detailed strategies (regional,topic-based and those relating to defence) seem to be inadequate to dealwith the current situation not only in the direct neighbourhood of the EUbut also outside it. The aim of the article is to verify the assumption that theEuropean Union needs a profound change of the model of its foreign policy.The basis of this shall be a newly defined global strategy of foreign policy ofthe EU, w hich would at the same time address contemporary challenges anddangers. In order to verify this thesis, the introductory analysis of the previousEU strategies in the international relations (the instruments and policyin external relations) shall be made; moreover, the conditions and bases forthe formulation of a new strategic model need to be discussed. And finally,the EU foreign policy in chosen framework areas should be revised as well asrecommendations for the future EU foreign policy should be made.